Proceedings of the 7th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2019
DOI: 10.7712/120119.7041.19395
|View full text |Cite
|
Sign up to set email alerts
|

On the Soil-Structure Interaction in the Seismic Response of a Monitored Masonry School Building Struck by the 2016-2017 Central Italy Earthquake

Abstract: The paper discusses the effects of Soil-Foundation-Structure (SFS) interaction on the seismic response of the "Pietro Capuzi" school in Visso, a village located in the Marche region (Italy) that was severely damaged by the 2016-2017 Central Italy seismic sequence. The school is a two-story masonry structure founded on simple enlargements of its loadbearing walls, which are only partially embedded in the alluvial loose soil of the Nera river. The structure was monitored as a strategic building by the Italian Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
(10 reference statements)
2
7
0
Order By: Relevance
“…5.4. Furthermore, the reduction of experimental and numerical frequency in the quiet intervals between the couples of mainshocks (E1-E2 and E2-E3) as well as after mainshock E3 confirms the structural stiffness degradation related to damage accumulation and progression of nonlinear response (de Silva et al 2019). As a further corroboration of the relevance of soil-structure interaction, the degradation in the experimental frequency is better captured by the numerical CB model with respect to its FB counterpart.…”
Section: Comparisons At Local Scale: Recorded Versus Numerical Accelesupporting
confidence: 61%
“…5.4. Furthermore, the reduction of experimental and numerical frequency in the quiet intervals between the couples of mainshocks (E1-E2 and E2-E3) as well as after mainshock E3 confirms the structural stiffness degradation related to damage accumulation and progression of nonlinear response (de Silva et al 2019). As a further corroboration of the relevance of soil-structure interaction, the degradation in the experimental frequency is better captured by the numerical CB model with respect to its FB counterpart.…”
Section: Comparisons At Local Scale: Recorded Versus Numerical Accelesupporting
confidence: 61%
“…To date it has been demolished. The soil which the structure is built on is characterized by quite poor properties, as presented in [3], [4], [10] highlighting the possible role of soil-structure phenomena in the seismic response of the building as confirmed also by the identification of dynamic properties made by the Task 4.1 Workgroup [2] and other researcher through numerical studies [11]. To deepen the specific issue associated to the soil-structure interaction of Visso School, the geotechnical group coordinated by Prof. F.Silvestri from the University Federico II of Naples has been involved in the research activities of Task…”
Section: The "Pietro Capuzi" School Of Visso (Mc)mentioning
confidence: 99%
“…In the following only a brief overview on the type of results achieved is presented while more detailed outcomes are illustrated in ([2], [3], [4] and [5]) for the Visso School and in [8] for the Fabriano Courthouse respectively. a.…”
Section: Modeling For the Numerical Simulation Of The Actual Responsementioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study on instrumented buildings in California (USA) showed that the torsional responses of the supporting structure and/or the in-plane flexibility of floor diaphragms can increase by not negligible factors the seismic-induced force demands on elastic acceleration-sensitive non-structural components . Similarly, it is known that soil-structure interaction (SSI) can affect the acceleration response of the buildings (e,g, Karapetrou et al, 2015;Karatzetzou et al, 2015;de Silva et al, 2019;Fathi et al, 2020;Oz et al, 2020, Hamidia et al, 2021Brunelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%